Self-rated reflective capacity in post-registration specialist nursing education students. Issue 5 (3rd September 2022) - Gabrielsson, Sebastian; Engström, Åsa; Lindgren, Britt-Marie; Molin, Jenny; Gustafsson, Silje
ABSTRACT: This study aimed to describe self-rated reflective capacity in students enrolled in post-registration specialist nursing education at the advanced level. We applied a non-experimental and cross-sectional design. A survey of 156 specialist nursing students at two universities in Northern Sweden was conducted. Data were collected in 2019 using a web-based questionnaire assessing self-rated reflective capacity through the Reflective Capacity Scale of the Reflective Practice Questionnaire. Data were analyzed descriptively using frequencies and proportions. Correlations were analyzed using Spearman's rho. Results show that students specializing in psychiatric care and oncological care report a higher reflective capacity than students specializing in other areas. We found no significant correlations between reflective capacity and gender, and reflective capacity in total did not correlate with age or work experience. We conclude that reflective capacity might vary between nursing students in different areas of specialization. Further research is needed to understand causes and impacts of variations in nursing students' reflective capacities.